Barron's practice exercises for the toefl - Sharpe, Pamela J. (Trẻ, 2003)
Practice exercises in this up-to-date manual apply all three TOEFL formats—the Paper-Based TOEFL, the Computer-Based TOEFL, and the new-generation CBT2. More than 1,000 items with explanatory answers and example answers are presented for the Listening, Speaking, Structure, Reading, and Writing sections of the TOEFL. A New-Generation TOEFL practice test with evaluation is included. Written by an experienced and widely respected ESL educator, this manual presents intensive TOEFL preparation.